The impact of cosmic-ray heating on the cooling of the low-metallicity interstellar medium - Brugaletta, Vittoria; Walch, Stefanie; Naab, Thorsten; Girichidis, Philipp; Rathjen, Tim-Eric; Seifried, Daniel; Nürnberger, Pierre Colin; Wünsch, Richard; Glover, Simon (Monthly notices of the Royal Astronomical Society, 2025)
Low-metallicity environments are subject to inefficient cooling. They also have low dust-to-gas ratios and therefore less efficient photoelectric (PE) heating than in solar-neighbourhood conditions, where PE heating is one of the most important heating processes in the warm neutral interstellar medium (ISM). We perform magnetohydrodynamic simulations of stratified ISM patches with a gas metallicity of 0.02 Z$_\odot$ as part of the SILCC project. The simulations include non-equilibrium chemistry, heating, and cooling of the low-temperature ISM as well as anisotropic cosmic-ray (CR) transport, and stellar tracks. We include stellar feedback in the form of far-ultraviolet and ionizing (FUV and extreme ultraviolet, EUV) radiation, massive star winds, supernovae, and CR injection. From the local CR energy density, we compute a CR heating rate that is variable in space and time. In this way, we can compare the relative impact of PE and CR heating on the metal-poor ISM and find that CR heating can dominate over PE heating. Models with a uniform CR ionization rate of $ζ$ = 3 $×$ 10$^{-17}$ s$^{-1}$ suppress or severely delay star formation, since they provide a larger amount of energy to the ISM due to CR heating. Models with a variable CR ionization rate form stars predominantly in pristine regions with low PE heating and CR ionization rates where the metal-poor gas is able to cool efficiently. Because of the low metallicity, the amount of formed stars in all runs is not enough to trigger outflows of gas from the mid-plane.